One Year Clinical Evaluation of E-max Press Crowns Retained with Fiber Reinforced Composite Post Versus E-max Press Endocrowns in Anterior Endodontically Treated Teeth (A Randomized Clinical Trial) - Abou El-Enein, Yasmin Hesham; Elguindy, Jylan Fouad; Zaki, Amina Abd El Latif (Brazilian Dental Science, 2021)
Objective: The purpose of this study was to assess patient satisfaction, gross fracture and marginal adaptation of e.max press endocrowns versus e.max press crowns retained with Fiber reinforced composite post (FRCP) and core in upper anterior teeth. Material and methods: The present study included 24 patients seeking root canal treatment in anterior upper arch. The patients received root canal treatment (RCT) then they were randomly assigned into two groups (n=12). The first group received preparation for the IPS e.max crowns retained with FRCP and core and the second group received preparation for the IPS e.max endocrowns. Press technique was used for the fabrication of both restorations using IPS e.max press ingots. Marginal integrity and gross fracture were evaluated using USPHS criteria and a questionnaire was conducted to evaluate patient satisfaction. Data were analyzed using IBM SPSS Statistics for Windows, Version 23.0. Armonk, NY: IBM Corp. Results: There was no statistical significant difference regarding gross fracture of both groups after 12 months (p-value = 0.093, Effect size = 0.447), meanwhile; group 1 was statistically significantly higher than group 2 regarding marginal integrity (p-value = 0.037, Effect size = 0.513). Regarding patient satisfaction FRCP and core group showed statistical significant higher satisfaction than endocrown group (p-value = 0.047, Effect size = 0.447). Conclusion: E.max press endocrowns revealed successful performance similar to e.max press crowns retained with FRCP in terms of gross fracture, however better marginal adaptation and patient satisfaction was obtained with e.max press crowns retained with FRC post and core group. Keywords Anterior teeth; Endocrown; Endodontically treated teeth; Fiber Post; E.max.